Maternal health challenges experienced by adolescents; could community score cards address them? A case study of Kibuku District- Uganda - Rebecca R. Apolot; Moses Tetui; Evelyne B. Nyachwo; Linda Waldman; Rosemary Morgan; Christine Aanyu; Aloysius Mutebi; Suzanne N. Kiwanuka; Elizabeth Ekirapa (BMC, 2020)
Abstract Introduction Approximately 34.8% of the Ugandan population is adolescents. The national teenage pregnancy rate is 25% and in Kibuku district, 17.6% of adolescents aged 12-19 years have begun child bearing. Adolescents mothers are vulnerable to many maternal health challenges including; stigma, unfriendly services and early marriages. The community score card (CSC) is a social accountability tool that can be used to point out challenges faced by the community in service delivery and utilization and ultimately address them. In this paper we aimed to document the challenges faced by adolescents during pregnancy, delivery and postnatal period and the extent to which the community score card could address these challenges. Methods This qualitative study utilized in-depth interviews conducted in August 2018 among 15 purposively selected adolescent women who had given birth 2 years prior to the study and had attended CSC meetings. The study was conducted in six sub counties of Kibuku district where the CSC intervention was implemented. Research assistants transcribed the audio-recorded interviews verbatim, and data was analyzed manually using the framework analysis approach. Findings This study found five major maternal health challenges faced by adolescents during pregnancy namely; psychosocial challenges, physical abuse, denial of basic human rights, unfriendly adolescent services, lack of legal and cultural protection, and lack of birth preparedness. The CSC addressed general maternal and new born health issues of the community as a whole rather than specific adolescent health related maternal health challenges. Conclusion The maternal health challenges faced by adolescents in Kibuku have a cultural, legal, social and health service dimension. There is therefore need to look at a multi-faceted approach to holistically address them. CSCs that are targeted at the entire community are unlikely to address specific needs of vulnerable groups such as adolescents. To address the maternal health challenges of adolescents, there is need to have separate meetings with adolescents, targeted mobilization for adolescents to attend meetings and deliberate inclusion of their maternal health challenges into the CSC.